Modeling of individual debris flows based on DEMNAS using Flow-R: A case study in Sigi, Central Sulawesi - Moch Hilmi Zaenal Putra; Indra Andra Dinata; Imam Achmad Sadisun; Dwi Sarah; Atin Nur Aulia; Sukristiyanti Sukristiyanti (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2022)
On 2018 September 28, 18:03 a local time (10:03 am UTC), the Mw 7.5 earthquake with a focal depth of about 20 km devastated the Palu region in Central Sulawesi, Indonesia resulting in a catastrophic disaster and many casualties. The Palu earthquakes triggered widespread landslides upstream, contributing to the sizeable material volume accumulated in rivers and mountain slopes. After the Palu earthquake, from September 28, 2018, until December 2021, at least 24 events of debris floods have occurred, which have spread to 15 villages. As of late, the empirical debris flow model Flow-R, software for susceptibility mapping of debris flows at a regional scale, was published. While Flow-R's applicability on a regional scale has been confirmed in several studies, the calibrated case using back-analysis of individual debris flow events in Indonesia based on DEMNAS with a spatial resolution of 8.3 m has never been conducted. Local debris flows modeling using Flow-R was evaluated with three well-documented debris flow events on the break slopes on the west and east sides of the Palu Valley. Quantitative analysis was carried out in this study to assess the accuracy, positive predictive value, and negative predictive value of models. First, the result shows the individual back-analysis model of debris flows found good agreement between debris-flow paths predicted and documented debris flow path extent. However, the parameters for rheological properties and erosion rate required in the software are limited. Second, the quantitative analysis shows accuracy, positive, and negative predictive value, which varies considerably. Based on the study, Flow-R is not suitable for comprehensive hazard mapping but provides a direct information about possible run-outdebris flow paths. Furthermore, lateral spreading and friction of Flow-R model results can be used to calibrate the process with rheological properties and erosion rate in other numerical modeling software, either for forward or back analysis.